Proses Penciptaan Nabi Adam dalam Hikayat Surat Al-Anbiya’: Analisis Perbandingan Antara Tradisi Kesusasteraan Melayu Tradisional & Kisah Dalam Al-Quran: The Creation Process of Prophet Adam in Hikayat Surat Al-Anbiya’: A Comparative Analysis Between Traditional Malay Literary Tradition & The Stories in The Qur’an - Mohd Zabidi, Ahmad Zahiruddin; Wan Abdullah, Wan Nasyrudin; Haris, Abu Hanifah; Nasir, Khairulnazrin (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
The Malay Islamic Hikayat is a genre of oral and written literature from the tradition of Traditional Malay Literature. Among the themes of this genre are stories of prophets and messengers that are told as single or group stories. Examples of unique stories in this genre include the Hikayat Nur Muhammad, Hikayat Bulan Berbelah, Hikayat Nabi Bercukur, Hikayat Nabi Mi’raj, Hikayat Nabi Wafat, Hikayat Nabi Yusuf, Hikayat Nabi Sulaiman and others. Among the stories written in this genre that collectively narrate the stories of the prophets and messengers is the story of Surat al-Anbiya’, which brings together 33 stories of the prophets and messengers in one manuscript. Although these stories are originally fables, in the religious context of the Malay Archipelago, the story of the prophets and messengers in this version of the fable has been accepted as authentic because the difference between the fable version and the Qasas Qur’ani version is not recognized. This study will discuss the development of the writing of The Malay Islamic Hikayat in the genre of stories of the Prophets and Messengers, as well as conduct content analysis and comparative analysis of the selected story, specifically the story of the creation process of Prophet Adam. The story of the events of Prophet Adam from the story of Surat al-Anbiya’ will be analyzed and compared with the story from the book Kisah Shahih Para Nabi (Sahih Qasas al-Anbiya’), the original work of Ibn Kathir (701-774H) summarized by Salim ‘Ied al-Hilali. This comparative analysis aims to identify the similarities and differences between the story of the creation of Prophet Adam in The Malay Islamic Hikayat version and the Qasas Qur’ani version. This study found that the stories attributed as revelations from Allah SWT, with the use of the term “Firman Allah” (Word of Allah) at the beginning of the story, are mostly non-Quranic verses.